Clopidogrel-Associated Thrombotic Thrombocytopenic Purpura following Endovascular Treatment of Spontaneous Carotid Artery Dissection - Rubano, Jerry A.; Chen, Kwan; Sullivan, Brianne; Vosswinkel, James A.; Jawa, Randeep S. (Journal of Neurological Surgery Reports, 2015)
Thrombotic thrombocytopenic purpura (TTP) is a life-threatening multisystem disease secondary to platelet aggregation. We present a patient who developed profound thrombocytopenia and anemia 8 days following initiation of therapy with clopidogrel after stent placement for carotid artery dissection. She did not have a disintegrin and metalloproteinase with thrombospondin domain 13 (ADAMTS 13) deficiency. Management included steroids and therapeutic plasma exchange. Clopidogrel has rarely been associated with TTP. Unlike other causes of acquired TTP, the diagnosis of early clopidogrel-associated TTP is largely clinical given the infrequent reduction in ADAMTS 13 activity.
Keywords: clopidogrel; TTP; carotid; stent; thrombocytopenia